Discursive Strategies of Ethnic Identity Construction in Nigeria Media Representation of Unknown Gunmen (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This study examines the media representation of unknown gunmen in Nigeria, focusing on the lexical and grammatical features and the discursive strategies. It also explores the implications of these strategies for ethnic identity construction. Drawing on Media Framing Theory, the research aims to identify the linguistic features the media deployed in representing these subjects. The study also analyses the discursive strategies used and their impact on ethnic identity construction in Nigeria. The study reveals several notable lexical and grammatical features through a qualitative analysis of newspaper articles in Vanguard, Independent, Leadership and Daily Trust. Phrases and words such as "unknown gunmen," "terror," and "violence" are frequently used, emphasizing the mysterious and dangerous nature of the perpetrators and the impact of their actions. Passive voice constructions, modal verbs, collective pronouns, and strong adjectives intensify the portrayal of the gunmen and their attacks. Discursive strategies identified in the media representation include Othering, criminalization, and ethnicization. The newspapers portray the gunmen as outsiders and threats to social order. This study recommends promoting a fair and impartial justice system that ensures accountability for perpetrators of violence, regardless of their ethnic or social backgrounds.
Keywords: Media representation; unknown gunmen; discursive strategies; ethnic identity construction